Overall Store Price Image (OSPI), Antecedents, And Its Effect On Repurchase Intention - Liana V. Sihotang; Jeanne Ellyawati (Jurnal Manajemen, 2020)
This study aims to examine the influence of store price image which is consisting of price fairness images, price pleasure images, price rewards images, price value images on overall store price images (OSPI), and repurchase intentions. The study also examines the role of moderation variables, store image, and price sensitivity on the relationship between OSPI and repurchase intentions. Several 423 respondents were recruited using a purposive sampling method. The structured questionnaire was distributed offline to respondents using paper and pencil test techniques. Data is processed using variant-based SEM (SmartPLS). The results showed that all antecedent variables of store price images have a positive effect on OSPI. Furthermore, OSPI effect positively on repurchase intentions. The study findings show that store image and price sensitivity did not moderate the relationship between OSPI and repurchase intention. This study found interesting results that store image and price sensitivity are mediating variables.